MANAJEMEN KONFLIK DI LEMBAGA PENDIDIKAN ISLAM - Muhammad Mukhtar Syuaib; Mardia (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
Conflict is a natural process that is inherent in the nature of all relationships and can be overcome by constructive management. Conflict management in a positive direction requires a process and effort that is not easy. Conflict can be used as a stimulus to increase communication and quality of work, but it can also reduce the quality of one's performance if it cannot be controlled. Madrasas as educational institutions in carrying out the educational process and in achieving the desired vision cannot be separated from conflict so that it can become an inhibiting factor in achieving the goals that have been formulated together if not managed properly. This research is qualitative in nature because it is intended to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. The research model used is a case study model. Data collection in this study used participant observation, in-depth interviews, document studies and triangulation. The data analysis used involves three components of analysis, namely data reduction, data display, and verification. The results showed that the source of conflict at MTs DDI Kaluppang was due to a discrepancy or misunderstanding in communication or distortion of communication, the behavior of one of the personnel who was stubborn in imposing his will, and did not want to compromise on a joint decision that had been made. As for the steps taken in managing the conflict that occurred, namely by taking family steps, joint deliberations, being compromising on something controversial, being accommodative, being tolerant, and prioritizing togetherness values.